Effect of Financially Punished Audit and Feedback in a Pediatric Setting in China, within an Antimicrobial Stewardship Program, and as Part of an International Accreditation Process - Gong, Sitang; Qiu, Xiu; Song, Yanyan; Sun, Xin; He, Yanling; Chen, Yilu; Li, Minqing; Luo, Rui; He, Liya; Wei, Qing; Shen, Songying; Liu, Yu; et al. (Frontiers in Public Health, 2016)
Background: Prior authorization, audit & feedback, and pay for performance are three core “active” strategies of antimicrobial stewardship program (ASP), yet little is known about the individual or combined benefits of such programs, particularly in pediatric. Objectives: The aim of present study was to compare these core ASP strategies and determine the incremental effect of financially punished audit & feedback. Methods: During the journey to the Joint Commission International accreditation, a tertiary pediatric medical center performed two different hospital-wide stewardship interventions in succession. The first stage without formalized ASPs served as pre-intervention period, Jan 2011 to Apr 2011. The ASP used prior authorization alone during the First-intervention period, May 2011 to Sep 2011. In Oct 2011, financially punished audit & feedback was introduced, marking the start of the Second-intervention period, Oct 2011 to Nov 2012. We compared differences of the change in monthly average antibiotic use and expenditure on antibiotics before and after the ASP changes by using interrupted time series via dynamic regression. The main end points included the proportions of antibiotic prescriptions and expenditure on antibacterial relative to all medications. Results: Before the Second-intervention period, neither the proportion of antibiotic prescriptions nor that of expenditure on antibiotics declined significantly in both ambulatory and inpatient settings. After the introduction of financially punished audit & feedback, however, the proportion of both antibiotic prescriptions (β=-6.269, P<0.001, and reduction=59.4% for outpatients; β=-1.235, P<0.001, and reduction=19.8% for inpatients) and expenditure on antibiotics (β=-7.777, P<0.001, and reduction=46.7% for outpatients; β=-4.933, P=0.001, and reduction=16.3% for inpatients) dropped immediately. Conclusion: The combination of more than one core strategies (prior authorization, audit & feedback, and pay for performance) will be more effective than one strategy alone.